Role of Helical Structure in MBP Immunodominant Peptides for Efficient IgM Antibody Recognition in Multiple Sclerosis - Staśkiewicz, Agnieszka; Quagliata, Michael; Real-Fernandez, Feliciana; Nuti, Francesca; Lanzillo, Roberta; Brescia-Morra, Vincenzo; Rusche, Hendrik; Jewginski, Michal; Carotenuto, Alfonso; Brancaccio, Diego; Aharoni, Rina; Arnon, Ruth; et al. (Frontiers in Chemistry, 2022)
The involvement of Myelin Basic Protein (MBP) in Multiple Sclerosis (MS) has been widely discussed in the literature. This intrinsically disordered protein has an interesting α-helix motif, which can be considered as a conformational epitope. In this work we investigate the importance of the helical structure in antibody recognition by MBP peptides of different lengths. Firstly, we synthesized the peptide MBP (81–106) (1) and observed that its elongation at both N- and C-termini, to obtain the peptide MBP (76–116) (2) improves IgM antibody recognition in SP-ELISA, but destabilizes the helical structure. Conversely, in competitive ELISA, MBP (81–106) (1) is recognized more efficiently by IgM antibodies than MBP (76–116) (2), possibly thanks to its more stable helical structure observed in CD and NMR conformational experiments. These results are discussed in terms of different performances of peptide antigens in the two ELISA formats tested.